Development and evaluation of different electroactive poly(vinylidene fluoride) architectures for endothelial cell culture - Durán-Rey, David; Brito-Pereira, Ricardo; Ribeiro, Clarisse; Ribeiro, Sylvie; Sánchez-Margallo, Juan A.; Crisóstomo, Verónica; Irastorza, Igor; Silván, Unai; Lanceros-Méndez, Senentxu; Sánchez-Margallo, Francisco M. (Frontiers in Bioengineering and Biotechnology, 2022)
Tissue engineering (TE) aims to develop structures that improve or even replace the biological functions of tissues and organs. Mechanical properties, physical-chemical characteristics, biocompatibility, and biological performance of the materials are essential factors for their applicability in TE. Poly(vinylidene fluoride) (PVDF) is a thermoplastic polymer that exhibits good mechanical properties, high biocompatibility and excellent thermal properties. However, PVDF structuring, and the corresponding processing methods used for its preparation are known to significantly influence these characteristics. In this study, doctor blade, salt-leaching, and electrospinning processing methods were used to produce PVDF-based structures in the form of films, porous membranes, and fiber scaffolds, respectively. These PVDF scaffolds were subjected to a variety of characterizations and analyses, including physicochemical analysis, contact angle measurement, cytotoxicity assessment and cell proliferation. All prepared PVDF scaffolds are characterized by a mechanical response typical of ductile materials. PVDF films displayed mostly vibration modes for the a-phase, while the remaining PVDF samples were characterized by a higher content of electroactive β‑phase due the low temperature solvent evaporation during processing. No significant variations have been observed between the different PVDF membranes with respect to the melting transition. In addition, all analysed PVDF samples present a hydrophobic behavior. On the other hand, cytotoxicity assays confirm that cell viability is maintained independently of the architecture and processing method. Finally, all the PVDF samples promote human umbilical vein endothelial cells (HUVECs) proliferation, being higher on the PVDF film and electrospun randomly-oriented membranes. These findings demonstrated the importance of PVDF topography on HUVEC behavior, which can be used for the design of vascular implants.